Water wave resonance in the new basin in Los Monjes del Sur, Venezuela - Solana, Pedro; Flores, Henry; Contramaestre, Hugo (Rev. Téc. Fac. Ing. Univ. Zulia)
Experimental wave oscillations on a physical model of the new basin formed by the junction of the two Islas del Sur of the Archipelago of Los Monjes, at the north of the Golfo de Venezuela are presented in this study. The experimental results indicate that for the prevailing wave conditions the oscillations in the basin are not significant, whereas, for storm wave conditions, specially those coming from the north, the oscillations are too high, in some cases overcoming the incident wave height. This suggests the posibility of resonance wave occurrence. Additional tests are performed and they are compared with a simplified long wave theory in order to check its appearance.